IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM BENTUK UPAYA MENINGKATKAN KEPEDULIAN SISWA SMP MUHAMMADIYAH 3 TERHADAP LINGKUNGAN SEKITAR MELALUI SEMINAR LINGKUNGAN - Septiana, Tina; Yulianti, Siska Dwi; Fauziyah, Siti Sarah; Susanto, Eko (MAJU : Indonesian Journal of Community Empowerment, 2024)
Garbage is the remains of human daily activities or natural processes in solid or semi-solid form in the form of organic or inorganic substances that are biodegradable or non-biodegradable which are considered useless and disposed of into the environment. As representatives of the future society, students must be equipped with the value of caring for the environment from an early age. This community service program uses the lecture and question and answer method in the form of a seminar with the theme "Environment: Green Environmental Care School for Muhammadiyah 3 Middle School Students in Sukamaju Village, Kadudampit District, Sukabumi Regency" with the aim of providing knowledge to Muhammadiyah 3 Middle School students about the need for awareness to protect the surrounding environment from damage that they can start from the school environment. Thus, students can contribute to the formation of green schools in their respective schools.